Wills and Inheritance in Modern Society: Emerging Challenges and Evolving Dynamics - nadia (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2024)
This paper discusses the phenomenon of wills and inheritance in modern society, which faces various challenges and new dynamics influenced by shifts in family structure, changes in gender roles, and geographical mobility. This study aims to analyse how these changes affect the distribution of inheritance and cause family conflicts. The research method used is a library study, reviewing relevant literature from various sources, including academic journals, books, and legal articles. The results of the study show that the shift from extended families to nuclear families, as well as the increased role of women in the family economy, has changed the dynamics of inheritance distribution. In addition, high geographical mobility poses challenges in coordination and communication among heirs. The dualism of inheritance law in Indonesia, namely Islamic law and customary law, also adds complexity to the distribution of inheritance. Community-based legal education has proven effective in improving public understanding of inheritance law and reducing conflicts. This study concludes that adaptation and harmonisation between traditional law and modern needs are essential to ensure fair and effective inheritance distribution in the modern era.